As escolas elementares rurais no Ceará : paisagens e protagonismo na fazenda Almas – Cariré (1940-1950) - Ribeiro Júnior, Raimundo Gomes (2013)
This research in a proposal for a study of the history and memory of brazilian education is based on finding the primary genesis of elementary rural schools in Ceará and propose an anderstanding of them. It has as starting point the elementary school of the old farm Almas in the municipality of Cariré north of state. Our goal is to understand the functioning of that school and its interface with culture rooted in semiarid landscapes typically from northeast. Traversing these paths we find the answers to same questions of our research, especially that one which seeks to justify the reasons that made those schools the protagonists of rural primary educacion during the twentieth century in our state. Our aim is to study from the educational developments in Brazil, despite the lack of resources, the importance of those schools houses, recognizing that many of them have emerged as an alternative to the education of populations in which the absence of conditions made impossible the displacement to other locations. In this way we contribute from our questions with the understanding of other teaching units and reflections of misguided policies that have been promoted in rural primary school. Then a typically urban education program without however meet the real needs of those populations beyond the suffering caused by the lack of assistence even lived with a social setting aggravated by long periods of drought.